Need Assessment Pengembangan Keprofesionalan Berkelanjutan Guru Smk Teknik Audio Video - Djoko Santoso (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
The objectives of the study were to (1) analyse the competence of Audio Video Engineering teachers of Vocational High Schools in Yogyakarta, Sleman and Kulonprogro; (2) assess the teachers’ continuing professional development (CPD) needs and (3) identify CPD programmes to accomodate the needs. The study employed a survey approach. The results of this study revealed the following: (1) the teachers’ competence in good, fair, and poor categories were 43.33%, 40%, and 16.67% respectively, thus it is crucial for the stakeholders to promote CPD ; (2) the teachers’ CPD needs in very good, good, and fair categories were 36.67%, 36.67%, and 26.66% respectively. It should be the basis for the stakeholders in planning the CPD programmes, since the teachers were planning to initiate their professional development; and (3) the CPD programmes prioritized by the teachers were training, internet-based learning, collaborative works with relevant universities, and self- development in terms of professional competencies.